Possible results of non-native crayfish species introduction into Turkey - Harlioglu, Muzaffer Mustafa; Yonar, Serpil Mise (Ege Univ, Fac Fisheries, 2007)
Crayfish are consumed as a luxury food item in many parts of the World. The high economic importance of crayfish caused the translocation of some species (Procambarus clarkii, Pacifastacus leniusculus, Cherax destructor, C. quadricarinatus, Orconectes limosus, O. rusticus ve Astacus leptodactylus) from their natural habitats into different water resources. On the other hand, in general, the translocation of crayfish species gives rise to negative environmental effects and they are accepted as a nuisance creature in their new habitat. The main reason of crayfish introduction at the start is that economical benefits, but at the end, crayfish are distributed commonly as uncontrolled populations in water resources. The negative effects of crayfish introductions are disappearance of native species, distribution of diseases into new habitats, consumption of fish eggs, reduction of fish stocks, excess consumption of water plants and direct or indirect impacts on water invertebrates. For example, the introduction of the native species from North America into Europe had negative impacts on the native species populations. Similarly, approximately 7,000 ton/year A. leptodactylus was exported from Turkey to Europe before the crayfish plague was arrived to Turkey. Crayfish export was stopped between 1986 and 1990, and it was only 320 ton in 1991. Although there has been an increase in the harvest of A. leptodactylus in Turkey in recent years (2317 ton in 2004), there is a danger to import non-native crayfish species into Turkey in order to expand crayfish production. In conclusion, it is thought that non-native crayfish species introductions into Turkey must be certainly forbidden because of the fact that the observed negative impacts of non-native crayfish species introductions carried out in many parts of the world. However, in comparison to the other native crayfish species of Europe, A. leptodactylus is accepted as a better species for reproduction and rearing. It has also an economic importance in European markets. For these reasons, to increase crayfish production of Turkey, before thinking the introduction of any non-native crayfish species it is necessary to increase studies scientifically on the biology, ecology, reproduction, feeding, juvenile rearing, conservation of populations, and diseases of A. leptodactylus.
Keywords: Astacus leptodactylus; freshwater crayfish; introduction; non-native species; Turkey